2015
DOI: 10.1161/hypertensionaha.115.05610
|View full text |Cite
|
Sign up to set email alerts
|

B-Type Natriuretic Peptide Deletion Leads to Progressive Hypertension, Associated Organ Damage, and Reduced Survival

Abstract: Altered myocardial structure and function, secondary to chronically elevated blood pressure, are leading causes of heart failure and death. B-type natriuretic peptide, a guanylyl cyclase A agonist, is a cardiac hormone integral to cardiovascular regulation. Studies have demonstrated a causal relationship between reduced production and/or impaired B-type natriuretic peptide release, and the development of human hypertension. However, the consequences of B-type natriuretic peptide insufficiency on blood pressure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
46
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 53 publications
6
46
0
Order By: Relevance
“…QT interval on the ECG is a measure of the total duration of ventricular activation and recovery, and it corresponds to the duration of the ventricular action potential [24] . In this study, similar to the previous reports, HF rats had significantly prolonged QT interval [25,26] . Although HDAC inhibitors have been shown to prolong the QT interval [27] , we did not detect a prolonged QT interval in the HF rats treated with 50 mg/kg of MPT0E014.…”
Section: Discussionsupporting
confidence: 92%
“…QT interval on the ECG is a measure of the total duration of ventricular activation and recovery, and it corresponds to the duration of the ventricular action potential [24] . In this study, similar to the previous reports, HF rats had significantly prolonged QT interval [25,26] . Although HDAC inhibitors have been shown to prolong the QT interval [27] , we did not detect a prolonged QT interval in the HF rats treated with 50 mg/kg of MPT0E014.…”
Section: Discussionsupporting
confidence: 92%
“…Studies on BNP knock-out rats have shown a critical role of BNP on blood pressure control and the regulation of cardiac hypertrophy pathways, with young adult BNP knock-out rats developing left ventricular cardiac hypertrophy that precedes hypertension. Moreover, the knock-out rats showed progressive nephropathy [15]. In addition to the natriuretic peptide system that we show here to be disrupted in stressed Pkd2 +/− mice, it will be important to monitor other systems that are markedly disturbed in stress conditions, such as the catecholaminergic and RAAS systems.…”
Section: Discussionmentioning
confidence: 99%
“…The cardiomyocyte cross‐sectional area of RV was significantly smaller in AD group than those in AV group ( P < 0.05) (Figure A). Meanwhile, myocardial mRNA expressions of ANP and BNP, known as myocardial hypertrophy markers, were significantly up‐regulated in RV of AV group ( P < 0.01 vs S), mRNA expression of ANP in RV was significantly down‐regulated in AD group compared to AV group, while ANP and BNP expressions were similar among groups in LV (Figure B). We also observed the perivascular coronary fibrosis and found that the perivascular fibrosis ratio was similar among groups ().…”
Section: Resultsmentioning
confidence: 92%